Asas Mabda’ Ar-Radha’iyyah Dalam Keabsahan Perjanjian Over Kredit KPR Syariah: Mabda' Ar-Radha'iyyah Principles on The Validity of Sharia Mortgage Over Credit Agreements - Jamil, Nury Khoiril Jamil; M. Ghufron; Abd. Syakur (ISTIDLAL, 2023)
The research focuses on the over-credit phenomenon which is often carried out due to customers' inability to carry out obligations or other reasons for Sharia KPR agreements in Indonesia. This phenomenon is important to study in order to determine legal certainty regarding the agreement between the giver and recipient of overcredit which ultimately does not cause losses for either party. This research focuses on two topics that will be studied, namely, first, related to the characteristics of Sharia KPR over-credit agreements in Indonesia, second, related to the validity of Sharia KPR over-credit agreements from the perspective of the Mabda' Ar-Radha'iyyah Principle. This research uses a normative research type with a statutory and regulatory approach and a conceptual approach. This research produces an analysis that, first, there are 2 (two) types of over-credit agreements in Indonesia, namely under-the-hood and legal procedural. Especially in this type of over-credit under the hand, it is an agreement with a new party without prioritizing good faith, especially towards the bank. Second, the validity of a sharia contract is assessed from the consent of the parties. One important element in consent is shown by the presence of complete information, which is an element of openness in the contract. In the context of over-credit carried out privately, this element is not achieved until the contract becomes invalid (fasakh) and the validity of the actions of the giver and recipient of over-credit becomes null and void and has no legal force.